Application of Islamic Community Development Preaching towards the Family Hope Program in Lakawali Village, Malili District, East Luwu Regency. - Yusuf, Abd Jabbar; Amin, Muliyati; Tajibu, Kamaluddin (Jurnal Mercusuar, 2020)
The main problem of this research is how to develop the Islamic community through the Family Hope Program (PKH) (Study on the development of the Islamic community in Lakawali Village, Malili District, East Luwu Regency). The problem is divided into three sub-problems: 1) What is the form of the Family Hope Program (PKH) in the development of the Islamic community in Lakawali Village, Malili District, East Luwu Regency? 2) How is the application of Islamic outreach in the development of the Islamic community related to the Family Hope Program in Lakawali Village, Malili District, East Luwu Regency? This is a descriptive qualitative research with a sociological and communication approach. Data sources are obtained directly from the community, agencies, and facilitators/dai in Lakawali Village, Malili District, East Luwu Regency, and data collection methods include observation, interviews, documentation, and literature review. The data is processed and analyzed through data reduction, data presentation, and conclusion drawing. The results show that: 1) The Family Hope Program in the development of the Islamic community is one form of poverty alleviation by the Ministry of Social Affairs that aims to improve education, health, and economic aspects. 2) The Islamic outreach activities carried out in the development of the Islamic community include monthly group meetings to monitor the development of the community’s morality, behavior, values, and religious norms.